Assessing WRF Model Performance for a Severe Case of Rainfall in Western Saudi Arabia - Samman, Ahmad; Abdaldym, Abdallah; Morsy, Mostafa (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
This study investigates the performance of the Weather Research and Forecasting (WRF) model in simulating a severe weather event, characterized by intense rainfall and thunderstorms, that occurred over western Saudi Arabia on May 8, 2014. During this event, Makkah meteorological station recorded approximately 50 mm of rainfall accompanied by thunderstorms, posing significant forecasting challenges. The model was configured with moderate-resolution settings and various parameterizations to simulate the event, and its results were compared with observed meteorological data. Key model outputs, including precipitation intensity and distribution, were analyzed to assess the model’s accuracy and its capability to capture critical atmospheric dynamics associated with heavy rainfall in arid regions. The simulated rainfall in the control experiment depicts is in good agreement with Tropical Rainfall Measurement Mission (TRMM) rainfall estimates in terms of intensity as well as spatio-temporal distribution. The findings highlight the strengths and limitations of the model for severe weather prediction in western Saudi Arabia, providing insights into optimal configurations for forecasting similar events in the future.